Neuerwerbungen für die Gemäldegalerie 1972-1984 : Karlsruhe 1984. (Karlsruhe : Staatliche Kunsthalle, 1984)
Ackermann, Peter ; Antes, Horst ; Arnold, Klaus ; Baumeister, Willi ; Delacroix, Eugène ; Eliasz, Nicolaes ; Gérard, Marguerite ; Küchenmeister, Rainer ; Léger, Fernand ; Nay, Ernst Wilhem ; Schultze, Bernard ; Tàpies, Antoni ; Thoma, Hans ; Vermeyen, Jan ; Wolf, Gustav ; etc.
boek